2018
DOI: 10.1182/blood-2018-99-117235
|View full text |Cite
|
Sign up to set email alerts
|

Baseline PET-Derived Metabolic Tumor Volume Metrics Did Not Predict Outcomes in Follicular Lymphoma Patients Treated with First-Line Immunochemotherapy and Antibody Maintenance in the Phase III GALLIUM Study

Abstract: Introduction: Evidence suggests that baseline 18fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography-derived parameters, such as metabolic tumor volume (MTV) and maximum standardized uptake value (SUVmax), may predict progression-free survival (PFS) in patients (pts) with follicular lymphoma (FL) treated with first-line R-CHOP immunochemotherapy. However, data from pts routinely treated with bendamustine or antibody maintenance are lacking, and several methods have been used to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…While TMTV, a surrogate marker of tumor cell burden, was unrelated to baseline SUVmax or patient outcomes in our series, TMTV >510 cm 3 has been associated with a higher risk of treatment failure in FL patients. 6 However, this discrepancy could be related to the absence of maintenance treatment in the study by Meignan et al 6 Considering that the long-term results of the PRIMA study showed improved PFS in FL patients receiving rituximab maintenance (10.5 years compared to 4.1 years without maintenance treatment) 33 , and the GALLIUM study 34 showed an additional benefit of obinutuzumab over rituximab for PFS, anti-CD20 maintenance could mitigate the prognostic value of TMTV at baseline. Accordingly, TMTV had no prognostic value in either arm (rituximab or obinutuzumab) of the GALLIUM study.…”
Section: Discussionmentioning
confidence: 99%
“…While TMTV, a surrogate marker of tumor cell burden, was unrelated to baseline SUVmax or patient outcomes in our series, TMTV >510 cm 3 has been associated with a higher risk of treatment failure in FL patients. 6 However, this discrepancy could be related to the absence of maintenance treatment in the study by Meignan et al 6 Considering that the long-term results of the PRIMA study showed improved PFS in FL patients receiving rituximab maintenance (10.5 years compared to 4.1 years without maintenance treatment) 33 , and the GALLIUM study 34 showed an additional benefit of obinutuzumab over rituximab for PFS, anti-CD20 maintenance could mitigate the prognostic value of TMTV at baseline. Accordingly, TMTV had no prognostic value in either arm (rituximab or obinutuzumab) of the GALLIUM study.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, FDG-PET analysis of the phase 3 GALLIUM study (58% treated by bendamustine induction), in which all patients received anti-CD20 antibody maintenance, found no association with either TMTV or SUV max . 6 Intriguingly, high pretherapy SUV max was associated with shorter PFS in nonanthracycline-treated (mainly bendamustine or lenalidomide) but not in anthracycline (R-CHOP)-treated patients in another study. 7 The predictive utility of a pretherapy T-effector gene signature in patients treated with CHOP/CVP (cyclophosphamide, vincristine, prednisone)-rituximab/obinutuzumab is reversed in patients treated with bendamustine-rituximab (B-R)/obinutuzumab.…”
Section: Glucose-avid Intratumoral T Cells Influence Pretherapy Suv Max In Flmentioning
confidence: 93%
“…Pretherapy FDG-PET scans were assessed for SUV max , TMTV, and total lesion glycolysis (TLG), using customized software (MIM Software, Cleveland, OH). 6,14,15 Biopsy samples (formalin-fixed, paraffinembedded tissue and tumor-infiltrating lymphocytes [TILs] from deaggregated nodes) were used for multiplex gene hybridization, immunohistochemistry, T-cell receptor (TCR) repertoire sequencing and flow cytometry as published. 12,[16][17][18][19] Cryopreserved TILs were used to assess cellular glucose uptake by intratumoral CD4 1 T cells, CD8 1 T cells, and CD19 1 B cells, by using the fluorescently Data are expressed as the number (percentage) of patients in the subgroups, unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, a large body of data from the GALLIUM study suggests no association of maximum standardized glucose uptake value (SUVmax) with either histological transformation 11 or PFS. 12 There is marked heterogeneity in FDG uptake within patients which reflects metabolic activity of the malignant B cells as well as that of the microenvironment. 13 Likewise, the isolated analysis of bone marrow or blood infiltration is not appropriate for the diagnosis of FL.…”
Section: Clinical Features and Diagnostic Approachmentioning
confidence: 99%
“…17 The utility of PET has been demonstrated by identifying disseminated disease ultimately associated with a poorer outcome if treated as localized on the basis of CT-based staging. 17 The prognostic value of total metabolic tumor volume at diagnosis in FL remains debated 12,18 and the predictive value of automated software solutions for measuring total metabolic tumor volume 19 needs to be validated in prospective studies before being utilized in a standard manner in clinical practice. The prognostic value of end-of-induction PET response after first-line immunochemotherapy for FL 20,21,22 is now clear and provides a platform for PET-adapted therapies in current clinical trials.…”
Section: Stagingmentioning
confidence: 99%